Multi-party game and simulation in the withdrawal of rural homestead: evidence from China. Issue 3 (30th April 2021) - Song, Lei; Lyu, Ping; Cao, Yingui
Abstract : Purpose: The purpose of this study was to analyze the interest conflicts and strategy evolution process of various stakeholders in the process of homestead withdrawal, to reveal which key factors can balance the interests of all parties. Design/methodology/approach: The authors developed an evolutionary game theoretical framework for homestead withdrawal in Yujiang District, Jiangxi Province, China. The authors compared the dynamic process of strategy change in different situations based on system dynamics. Findings: Compared with indirect external factors, direct economic factors, such as increasing compensation standards or increasing fines, are more likely to encourage peasants to withdraw from their homesteads. The dynamic subsidy strategy can increase the probability of peasants withdrawing from their homestead. Additionally, awarding officials with promotions can effectively encourage local governments during the process. Originality/value: Previous studies have conceptualized farmers' willingness to withdraw from their homestead as a static process, ignoring the underlying dynamism. This paper analyzes the game mechanism among the stakeholders of the homestead withdrawal process from a dynamic perspective, to provide efficient suggestions regarding policymaking for homestead withdrawal.